Role of urine sediment cytology in the diagnosis of renal disorders in comparison with biochemical and histopathological findings - Bhagyalakshmi, A.; Sirisha, O.; Uma, P.; Devi, P. Urmila; Vijayababu, P. V. S. S.; Kasibabu, A. (International Journal of Research in Medical Sciences, 2017)
Background:The functional reserve of the kidney being large, serum biochemical parameters do not show abnormality until late. The need to recognize minimal damage in the kidneys is hence valuable. Urine sediment examination is cost effective, time saving and is called “liquid renal biopsy”. The present study was aimed to evaluate the role of urine sediment examination in predicting the severity of renal damage and compare the results with serum biochemical parameters, 24 hour urine protein values and renal biopsy findings. Methods:A total of 149 patients presenting with symptoms pertaining to renal disease were included in the study. Clinical information and serum biochemical parameters were obtained. Urine examination was done and renal biopsy performed in all the cases. 2 scoring systems were adopted to grade the urine sediment findings and renal biopsy grading devised by A. Z. Gyory et al. was used to grade the renal injury. 24 hour urine protein was estimated by Esbach’s method. Urine sediment scores, serum biochemical parameters, 24 hour urine protein values were compared with the grades of renal injury on renal biopsies and statistical significance calculated. Results:32.8% of patients with renal disease were in the age group of 31-40 years. Nephrotic syndrome was the most common clinical presentation (33.5%) followed by nephritic syndrome (21.4%). The most common histopathological diagnosis was post infectious glomerulonephritis (n = 26) followed by acute interstitial nephritis (n = 17). 14 cases of lupus nephritis were diagnosed all of which were confirmed by “full house” pattern of immunofluorescence. Both the urine sediment scores had high specificity and positive predictive values in predicting the severity of renal injury. 24 hour urine protein had high positive predictive value in predicting the severity of renal injury. Serum biochemical parameters were insignificant in predicting the severity of renal injury. Conclusion: Urine sediment examination can be used as an effective diagnostic test for predicting the severity of renal injury. The decision of further investigations and follow-up can be certainly decided by taking urine microscopy findings and 24 hour urine protein values into consideration.